Relation between right ventricular enlargement, QRS duration, and right ventricular function in patients with tetralogy of Fallot and pulmonary regurgitation after surgical repair. Issue 4 (1st October 2000) - El Rahman, M Y Abd; Abdul-Khaliq, H; Vogel, M; Alexi-Meskishvili, V; Gutberlet, M; Lange, P E
Abstract : OBJECTIVE: In patients with repaired tetralogy of Fallot, to examine (1) a possible relation between right ventricular enlargement and QRS prolongation, and (2) the effect of right ventricular enlargement caused by pulmonary regurgitation on the right ventricular ejection fraction, evaluated by three dimensional echocardiography, and global function, evaluated by the myocardial performance index. DESIGN AND PATIENTS: 40 patients with repaired tetralogy were studied. Right ventricular volumes were derived from three dimensional echocardiographic data after this method had been validated by comparison with magnetic resonance imaging in 21 patients. Ejection fraction was calculated from end diastolic and end systolic volumes. The Doppler derived myocardial performance index was measured in all patients. Measured data were correlated with QRS duration. SETTING: Tertiary cardiac centre for congenital heart disease. RESULTS: There was good agreement between three dimensional echocardiographic and magnetic resonance assessment of right ventricular volumes and ejection fraction. The z score of the right ventricular end diastolic volume and ejection fraction of all patients was 1.35 and −4.15, respectively. Patients with severe pulmonary regurgitation had a lower right ventricular ejection fraction (p < 0.01) and an increased myocardial performance index (p < 0.01) compared with patients with mild to moderate pulmonary regurgitation. The correlation between ejection fraction and right ventricular end diastolic volume was r  = −0.35 (p < 0.05). The mean (SD) QRS duration was 131.89 (25.69) ms, range 80–180 ms. The correlation between QRS duration and right ventricular end diastolic volume was r  = 0.6 (p < 0.01). CONCLUSIONS: There is a correlation between the right ventricular size obtained by three dimensional echocardiography and QRS duration on the surface ECG, indicating mechanoelectrical interaction. The severity of pulmonary regurgitation has a negative influence on right ventricular ejection fraction and combined systolic and diastolic global function, as assessed by myocardial performance.